Attenuation of ataxia telangiectasia mutated signalling mitigates age‐associated intervertebral disc degeneration. Issue 7 (21st June 2020) - Han, Yingchao; Zhou, Chao‐Ming; Shen, Hongxing; Tan, Jun; Dong, Qing; Zhang, Lei; McGowan, Sara J.; Zhao, Jing; Sowa, Gwendolyn A.; Kang, James D.; Niedernhofer, Laura J.; Robbins, Paul D.; et al.
Abstract: Previously, we reported that persistent DNA damage accelerates ageing of the spine, but the mechanisms behind this process are not well understood. Ataxia telangiectasia mutated (ATM) is a protein kinase involved in the DNA damage response, which controls cell fate, including cell death. To test the role of ATM in the human intervertebral disc, we exposed human nucleus pulposus (hNP) cells directly to the DNA damaging agent cisplatin. Cisplatin‐treated hNP cells exhibited rapid phosphorylation of ATM and subsequent increased NF‐κB activation, aggrecanolysis, decreased total proteoglycan production and increased expression of markers of senescence, including p21, γH2 AX and SA‐ß‐gal. Treating cisplatin‐exposed hNP cells with an ATM‐specific inhibitor negated these effects. In addition, genetic reduction of ATM reduced disc cellular senescence and matrix proteoglycan loss in the progeroid Ercc1 −/∆ mouse model of accelerated ageing. These findings suggest that activation of ATM signalling under persistent genotoxic stress promotes disc cellular senescence and matrix homeostatic perturbation. Thus, the ATM signalling pathway represents a therapeutic target to delay the progression of age‐associated spine pathologies. Abstract : Persistent DNA damage causes chronic activation of ATM signaling, leading to disc cellular senescence and degeneration. Attenuation of ATM signaling mitigates disc cellular senescence and intervertebral disc degeneration.